Platelet proteomics: from discovery to diagnosis. (3rd June 2018) - Looße, Christina; Swieringa, Frauke; Heemskerk, Johan W. M.; Sickmann, Albert; Lorenz, Christin
ABSTRACT: Introduction : Platelets are the smallest cells within the circulating blood with key roles in physiological hemostasis and pathological thrombosis regulated by the onset of activating/inhibiting processes via receptor responses and signaling cascades. Areas covered : Proteomics as well as genomic approaches have been fundamental in identifying and quantifying potential targets for future diagnostic strategies in the prevention of bleeding and thrombosis, and uncovering the complexity of platelet functions in health and disease. In this article, we provide a critical overview on current functional tests used in diagnostics and the future perspectives for platelet proteomics in clinical applications. Expert commentary : Proteomics represents a valuable tool for the identification of patients with diverse platelet associated defects. In-depth validation of identified biomarkers, e.g. receptors, signaling proteins, post-translational modifications, in large cohorts is decisive for translation into routine clinical diagnostics.